Assessment of the sustainable livelihood program: Employment facilitation process - Marife Magno-Ballesteros; Tatum Ramos; Jasmine Magtibay; Aniceto C. Orbeta; Gerald Daval-Santos; Ann Jillian Adona; Kathrina Gonzales (Philippine Institute for Development Studies (PIDS), 2016)
The Sustainable Livelihood Program - Employment Facilitation Track (SLP-EF Track) is a scheme that facilitates the employment of Pantawid Pamilyang Pilipino Program (4Ps) beneficiaries. The SLP-EF track has much potential to bring the 4Ps beneficiaries closer to reaching the poverty threshold because getting employed would provide additional income to the beneficiaries on top of the incentives provided to them by the 4Ps. For this to be realized, however, the SLP-EF track would have to be effective in targeting beneficiaries and in identifying employment partners for 4Ps. There is also a need for the Department of Social Welfare and Development to reassess its role in employment facilitation and to effectively link the 4Ps to other labor employment programs of government.
Keywords: 330; livelihood program; employment; poverty; Pantawid Pamilyang Pilipino Program